The code of silence: Transnational autonomy and oversight of signals intelligence - Ronja Kniep (Intelligence Oversight in Times of Transnational Impunity: Who Will Watch the Watchers?, 2023)
This chapter analyses intelligence and its oversight through the lens of transnational fields and symbolic domination. Using the cooperation of the German Bundesnachrichtendienst (BND) with the National Security Agency (NSA) as an example, it examines the extent to which the practices and power relations of signals intelligence (SIGINT) have destabilised or circumvented democratic oversight. This is illustrated by the struggles around two rules of the game in SIGINT: the distinction between domestic and foreign communication, and the Third Party Rule. In the post-Snowden discourse, the domestic–foreign distinction is transformed from a silent form of symbolic domination (doxa) into a contentious one (orthodoxy), opposed by a heterodox discourse of civil and human rights. While the definition of the Third Party Rule is unsettled through litigation, it continues to enable the relatively autonomous interaction among the players in the field – structurally akin to the omertà, the code of silence by the mafia.
Keywords: 300